The Role of the Wakaf Deed Issuer Official (PPAIW) in the Process of Issuing Wakaf Land Asset Certificates in the KUA of Japah District, Blora Regency - Ulfah, Ummi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
The purpose of this study is to determine the authority of PPAIW in issuing waqf certificates, obstacles that affect the authority of PPAIW and the solutions provided in issuing waqf certificates at the KUA of Japah District. The approach used is to determine and analyze the role of the Waqf Pledge Deed Making Officer (PPAIW) in the process of issuing waqf land asset certificates, both in terms of legal norms and their implementation in the field. The results of the study The role of PPAIW is the role of verifier, facilitator, educator, and mediator. The implementation of the PAIW role as a verifier, where the waqf administration requirements are in accordance with regulations. The implementation of the PAIW role as a facilitator in the implementation of the waqf pledge, as for the role of facilitator in the registration of waqf land has not been running well. The role as an educator has also not been implemented well by PAIW. Guidance and monitoring of nazir have also not been implemented. Likewise, the implementation of the role of the head of KUA as a mediator has not been implemented well. The obstacles encountered were the lack of PPAIW resources in the field of endowment law because all PPAIW in Japah District had never attended special PPAIW education and training. The lack of facilities and infrastructure to support the duties and functions of PPAIW, and the lack of public awareness and understanding regarding endowment law, resulting in the public having little concern in monitoring the performance of PPAIW and the performance of nazir.